Familial Currarino Syndrome - Jim C. Yip; Soundappan V.S. Soundappan; Andrew J.A. Holland (Elsevier, 2020)
A four-day-old girl was transferred to a tertiary pediatric center with bilious aspirates and abdominal distension. Examination found a previously unsuspected anorectal malformation with a perineal fistula. Radiography revealed a scimitar sacrum and ultrasound a tethered cord, sacrococcygeal dysplasia and bilateral hydroureteronephrosis. Magnetic resonance imaging detected a presacral mass measuring 3.5cm. The features of anorectal malformation, sacral defect and presacral mass suggested Currarino Syndrome, also associated with spinal cord and urogenital tract anomalies. The patient's mother, maternal aunt and two maternal cousins also had Currarino syndrome, with genetic testing confirming a pathological variant in the MNX1 gene. The patient was managed with resection of the presacral mass and concurrent posterior sagittal anorectoplasty. Histopathology diagnosed a mature teratoma with immature elements. As there is a risk of 1 in 2 children of patients with Currarino syndrome being affected, careful clinical examination and appropriate imaging should be performed at birth.